2019
DOI: 10.1186/s12913-018-3852-9
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a case management intervention for frequent users of the emergency department (I-CaM): an effectiveness-implementation hybrid trial study protocol

Abstract: BackgroundED overcrowding represents a significant public health problem in developed countries. Frequent users of the emergency departments (FUEDs; reporting 5 or more ED visits in the past year) are often affected by medical, psychological, social, and substance use problems and account for a disproportionately high number of ED visits. Past research indicates that case management (CM) interventions are a promising way to reduce ED overcrowding and improve FUEDs’ quality of life. There is, however, very limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…The external psychiatrist consultation service in the ED with CM was subject to negative evaluation from nurses in qualitative exploration. An integrated psychiatric unit may provide greater support to staff facing FUED psychiatric and behavioral issues, representing an important part of FUED care [ 17 ]. In addition, qualitative exploration revealed that CM activity was considered not visible enough.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The external psychiatrist consultation service in the ED with CM was subject to negative evaluation from nurses in qualitative exploration. An integrated psychiatric unit may provide greater support to staff facing FUED psychiatric and behavioral issues, representing an important part of FUED care [ 17 ]. In addition, qualitative exploration revealed that CM activity was considered not visible enough.…”
Section: Discussionmentioning
confidence: 99%
“…Email reminders were sent until at least a 60% [ 20 ] participation rate was achieved in both groups. All procedures were approved by the Swiss Ethics Committee (project number 2018–00442) [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a call from health authorities and hospitals in Switzerland for better care of FUEDs via interventions specifically adapted to them, such as the CM [24]. The importance of the FUEDs issue in Switzerland, as reported in various regional surveys [5,[25][26][27] and the scant information on the perceptions of local ED professionals [20] prompted us to conduct a survey at the national level among ED staff (medical doctors and nurses from different linguistic regions and EDs specialization levels) in order to evaluate: a) the extent to which FUEDs are perceived as an issue; b) their perceived levels of knowledge and understanding of FUEDs; c) levels of perceived usefulness of CM and interest in implementing this intervention in their ED service.…”
Section: Introductionmentioning
confidence: 99%
“…Further, two ongoing trials are helping advance the field. First, at the University of Lausanne, a multi-site trial called the I-CaM project (Implementing a Case Management Intervention for Frequent User of the Emergency Department) has been recruiting participants since 2018 [ 12 ]. The trial’s objectives are twofold: (1) to develop and implement a case management intervention tailored to frequent users across multiple EDs, and (2) to evaluate the implementation process and effectiveness.…”
mentioning
confidence: 99%